Preliminary Exploratory Study: Are HEPs Ready for Communication & Multimedia Micro Credentials Adoption in Malaysia? - Keoy, Kay Hooi; Javid, Iqbal; Ho, Meng Chuan; Ooi, Pei Boon *; Shaik, Shabana Anjum; Koh, Yung Jing; Yeo, Sook Fern; Teoh, Wai Yi; Kek, Lilian Siew Yick (IEEE, 2023)
Micro-credentials are officially recognized records that demonstrate the completion of learning objectives during shorter, less time-consuming educational or training events. They concentrate on validating competency-based knowledge, outcomes, and/or skills using trustworthy assessments and open standards, which can improve graduates' chances of finding employment. An institution or organization may accept microcredential for credit or as an attestation for potential employers. Initially, micro-credentials were first established in online discussion forums and other social media platforms to differentiate average users from advanced users by awarding digital badges to the respondents who completed the necessary assessments and assignments, for the purposes of upskilling, as well as learning new skills. This exploratory research seeks to provide an overview of micro credential adoption among Higher Education Providers in Malaysia